Housewives' Behavior Towards the Use of Plastic Bags in North Tapanuli, North Sumatra - Restu Auliani; Desy Lamtiur Kristin Tampubolon; Desy Ari Apsari; Nelson Tanjung; Julietta Br Girsang (Journal of Social Research, 2023)
Excessive use of plastic bags adversely affects health and the environment based on their hard-to-decompose nature. The increase in the number of plastic bag use is strongly influenced by population growth and changes in people's lifestyles, especially in shopping patterns among housewives, besides that government policies related to the Covid pandemic have triggered an increase in the use of plastic bags. This analytical observational research aims to determine the relationship between knowledge and attitudes of housewives towards the use of plastic bags in Pasar Siborongborong Village, North Tapanuli, North Sumatra, with a cross-sectional research design with an accidental sampling method. Interviews were conducted with 95 housewives. Data were analyzed using the Chi-Square test with CI:95%. The results of research on the use of plastic bags by housewives showed that 57.9% of the knowledge level of housewives in the good category, 64.2% of housewives' attitudes in the category were not good and 77.9% of the use of plastic bags in housewives was not good. The results of the Chi-Square test analysis showed that there was no meaningful relationship between the level of knowledge of housewives towards the use of plastic bags. (p.value: 0.864). On the other hand, there is a significant relationship between the attitude of housewives towards the use of plastic bags and the p.value: 0.010. Knowledge about the use and dangers caused by plastic bags can be done through socialization with the public, including through advertisements on television and social media. The implementation of restrictions on the use of plastic bags through the paid plastic bag policy at supermarkets is felt to have not been optimal in an effort to reduce the use of plastic bags.